Chemical composition and in vitro ruminal degradation of hay and silage from tropical grasses - Arroquy, Jose Ignacio; Cornacchione, Monica; Colombatto, Darío; Kunst, Carlos Roberto (2018)
This study was conducted to evaluate the effects of preservation type on chemical composition and in vitro ruminal degradation of warm-season grasses (WSG). Treatments consisted of two factors (6 2): the first factor was tropical grasses: Cenchrus ciliaris (cv. Biloela, and cv. Molopo), Chloris gayana (cv. Callide and cv. Finecut), Panicum maximum, and Brachiaria bryzanta; and the second factor was preservation type (hay vs. silage). Cell wall, hemicellulose, cellulose, and water-soluble carbohydrate (PB0.05) concentrations were different among WSG. In general, hay or silage altered fiber content compared with fresh. For instance, hemicellulose and cellulose contents were lower in silage than in hay and fresh grass (PB0.05). Gas production rates were higher in silage from 0 to 24 h of fermentation, except at 4 h of incubation. After 24 h, gas production (GP) rate was similar for both preservation types, whilst potential GP was similar between preservation types. However, silage had decreased lag time compared with hay (PB0.01). Silage had greater dry matter disappearance than hay (PB0.05), and gas production yield was similar for grass species and preservation type. Our results indicate that WSG conserved as silage showed beneficial changes in chemical composition and dry matter degradation compared with hay.